Role of Gut Hormones in Acutely Ill Patients - M Nematy; JE O'Flynn; AE Brynes; S Brett; GS Frost (Tehran University of Medical Sciences, 2005)
The nutritional status in patients in ITU appears to decline not only during their stay in ITU but long after discharge from ITU. The deterioration in nutritional status during and after ITU management is not fully understood. Re-establishing normal spontaneous feeding after critical illness is a vital component in the recuperative process. Gut released peptides, such as ghrelin and peptide YY (PYY) that regulate the initiation and termination of meals (Cummings et al. 2002, Batterham et al. 2002), could play a role in the altered eating behaviour patients. The aim of this study was to assess the pattern of ghrelin and PYY during the stay of ITU patients in hospital. 16 patients aged 60± 4.7yrs, BMI 28.1± 1.7kg/m2 (mean± SEM) admitted to ITU underwent fasting blood sample collections every second day throughout the first week on ITU and once a week thereafter until day 28 or discharge home. Changes in appetite, biochemical and anthropometric markers of nutritional status were recorded. Three fasting blood samples at least three days apart were collected from the 36 matched age and BMI healthy volunteers 54.3±2.9yrs, p=0.3 BMI 25.8±0.8kg/m2 P=0.2. As compared with healthy subjects, ITU patients exhibited a significantly lower level of ghrelin (day one 297±76.3 v. 919.8±88.3 pmol/l P